Pengembangan Media Pembelajaran Wordwall untuk Keterampilan Membaca Bahasa Jerman Siswa Kelas XI SMA - Ardinata, Davi; Pujosusanto, Ari (LATERNE, 2025)
The impetus for this research stems from the necessity for innovative learning media to facilitate German reading skills, a necessity that was identified through interviews conducted with German language teachers of class XI at SMAN 1 Tarik. Conventional methods, which rely exclusively on books as learning media, continue to be employed due to a paucity of innovative learning media alternatives. This situation contributes to a perception of monotony and boredom in the learning process. To address this concern, the Wordwall media was developed for learning German reading skills in class XI SMA. The central research question guiding this study is as follows: What is the process of developing Wordwall learning media for German reading skills of grade XI high school students?. The objective of this study is to elucidate the process of developing Wordwall learning media for German reading skills of XI grade high school students. The research method employed is the Research & Development (R&D) method. The data presented herein were obtained through interview instruments and validation questionnaires from media and material experts. In this study, Wordwall media development was carried out with the stages of analyze, design, development, and evaluation. The analyze stage is the stage where the researcher analyzes the problem through interviews with German language teachers of class XI SMAN 1 Tarik. In the subsequent design stage, the materials and media templates that will be developed according to the findings at the analysis stage are determined. The materials and templates are then developed into a complete media and assessed for feasibility by validators at the development stage. The results obtained from the material expert validation were 92.5%. The results obtained from the validation of two media experts were 82.5% and 90%. Subsequent to this, media revisions were executed in accordance with the criticisms and suggestions put forth by the validators during the evaluation stage. The findings indicate that Wordwall can be utilized as a learning media for German reading skills in grade XI SMA.